"Dinarte está morto?": narrativas e temporalidades na (re)construção de memórias sobre um agente político do Seridó potiguar (1980 - 1984) - Mariz, Francisco Félix da Silva (2023)
This dissertation has as its object the memories that Dinarte de Medeiros Mariz projected of himself throughout his public life, however, we are within a time frame from his death on July 9, 1980 in four, after spent two months hospitalized at the Hospital de Base in Brasília, DF, suffering from an intestinal hemorrhage. Dinarte Mariz was an outstanding politician in Rio Grande do Norte and Brazil and had a career ranging from mayor of Caicó, governor of Rio Grande do Norte to senator of the Federative Republic of Brazil. At the time of his death, a significant number of admirers and onlookers took to the streets of Natal and Caicó, which the newspaper Diário de Natal classified as a large crowd. The senator's body arrived in Rio Grande do Norte on a Brazilian Air Force – FAB – plane, where he received honors as head of state at the then RN Government Palace. After the final funeral in the capital, a FAB squadron brought the former mayor of Caicó together with family members and political allies for the last goodbye in the City of Caicó where he was buried. The referred politician in a masterful way led the construction of his memory, so that it becomes a great danger for a work about him to be trapped in the constructed memories. Therefore, this research seeks to interweave information about the memories of Dinarte Mariz who transited between the many events of Brazilian politics and, according to journalistic sources, was a tireless defender of dictatorial governments. However, there is a historical fact documented by the Diário de Natal newspaper that covered the dead senator's death, wake and seventh-day mass, which forms an important narrative of Dinarte Mariz's memory that was explored in this research.